Gestión empresarial y competitividad en la empresa de transportes Viajes & Turismo “Grupo Jaen Transportes E.I.R.L.”-2022 - Vásquez Torres, Melisa Silvana (2025)
The current research aims to develop and determine the current relationship between business management and competitiveness in the travel and tourism transport company "GRUPO JAEN TRANSPORTES E.I.R.L.", which was established in 2022. The type of research is applicative and was carried out carried out with a sample of twelve associates. It turns out that there is no direct and significant link between the variables under study, as demonstrated by the Rho Spearman correlation results of -0.018 and a significance value greater than 0.05, thus confirming that there is no relationship between both variables.